A RARE CAUSE OF SIDEROBLASTIC ANEMIA: TRNT1 MUTATION - Fatma Tuba YILDIRIM (Elsevier, 2021)
Case report: tRNA nucleotidyltransferase 1(TRNT1) gene encodes a polymerase involved in the maturation of cytosolic and mitochondrial transfer RNAs. Autosomal recessive loss of function mutations of TRNT1 leads sideroblastic anemia, immunodeficiency, fevers and developmental delay at varying degrees. Here we present a 10-year-old girl with periodic fever, retinitis pigmentosa, B cell deficiency, seizures and transfusion free sideroblastic anemia due to compound heterozygote TRNT1 mutation.